The Effect of Basic Fire Fighting Training and Instructor Experience on the Work Skills of Employees in the Fire Department of SKK Migas ENI Jakarta - Siahaan, Leonard; Due, Laurensius Reinald Diansilves; Putranto, Diyan; Milawati, Milawati; Togubu, Runi Yulianti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
A healthy and safe working environment is an important factor for every company. Workplaces with a lot of equipment connected to electrical outlets and the use of chemicals and gases make the risk of fire in the workplace much greater than in other places. Fires in the workplace can cause significant losses, including injuries, property damage, and even loss of life. Therefore, it is important to understand the potential dangers of fire, take preventive measures, and know how to respond to emergency situations. The purpose of this study was to determine the effect of basic firefighting training and instructor experience on the work skills of SKK Migas ENI employees in Jakarta. The research method used was a survey method. The analysis method used multiple linear regression analysis. The regression equation resulting from this study is Y = 11.386+0.216 X1+0.202 X2 + є. The coefficient of determination (R2) value is 0.426 (42.6%). The hypothesis test produced a calculated F value of 25.460 > Ftable 2.70. The results of the hypothesis test concluded that basic firefighting training and instructor experience partially and simultaneously had a positive and significant effect on the work skills of SKK Migas ENI employees in Jakarta.